The Effect of the Poster-Assisted AIR (Auditory Intellectually Repetition) Model on Sociology Learning Outcomes - Jihatul Hadi; Sukardi Sukardi; Nursaptini Nursaptini (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
The purpose of this research is to find out whether the AIR (Auditory Intellectual Repetition) mode1 assisted by poster media has an influence or not on sociology learning outcomes. Every student who is in class XI-IPS at SMAN 01 Wanasaba becomes the population in this study. Samples were taken by simple random sampling technique after class adjustment. The quasi-experimental type was used in this research method with a posttest only with nonequivalent control group design by utilizing two classes, namely the experimental class and the control class and giving a posttest without a pretest. The data collection method uses multiple choice objective tests that have been tested for validity, item difficulty level, reliability, effectiveness of the distractor and discriminating power. Two Independent Sample T test is used to analyze research data quantitatively. Based on the parametric test, it is evident that the poster-assisted AIR (Auditory Intellectually Repetition) model has an effect on sociology learning outcomes. Theoretically, this means that the use of the AIR (Auditory Intellectually Repetition) model will help strengthen learning theories, especially those based on constructivism and cognitivism